The Modified Crescenteric Anterior Intercostal Perforator Flap. Issue 5 (May 2020) - Denning, Max; Hayes, Philippa; Tsang, Fiona; Leff, Daniel; Thiruchelvam, Paul; Hadjiminas, Dimitri
Abstract : Summary: Lower pole breast cancers are challenging to manage because conventional wide local excision may produce a "bird's beak" deformity. In an era of oncoplastic surgery, techniques that balance oncological results with cosmetic outcomes such as local flaps have extended the role of breast-conserving surgery. Local flaps are particularly useful for partial breast reconstruction due to the relative simplicity of the surgical procedure and reduced morbidity. Intercostal artery perforator flaps have a shorter duration of surgery than free flaps and do not require microsurgical anastomoses. Anterior intercostal artery perforator (AICAP) flaps provide excellent cosmesis, yet traditional crescenteric harvest yields limited volume for reconstruction. We describe a modification to an established reconstructive technique for lower pole breast defects. The technique is based on 3 extensions of tissue, providing a larger volume of tissue replacement compared with traditional AICAP flaps. The technique is particularly suitable for small- and medium-sized non-ptotic breasts, with lower pole tumors. The modified crescenteric AICAP technique can be used to increase the available tissue when performing lower pole reconstructions. Abstract : Supplemental Digital Content is available in the text.